Complications of cardiovascular procedures : risk factors, management, and bailout techniques - Moscucci, Mauro. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"Provides interventional cardiologists, endovascular interventionalists, and physicians in training with a comprehensive resource on the prevention and management of complications in interventional cardiology. The book focuses specifically on risk factors, prevention, and management with conventional and/or with bailout techniques and devices. The textbook includes images of devices and other resources. The first section, on general principles, includes quality assurance, training requirements, legal considerations, adjunctive pharmacotherapy, and conscious sedation. Subsequent sections cover general complications of invasive procedures and complications of specific coronary interventions, noncoronary cardiac interventions, peripheral vascular procedures, pediatric interventions, and electrophysiology procedures. A companion website includes videos of over 100 complications and bailout techniques"--Provided by publisher.